2019
DOI: 10.1128/mra.01052-18
|View full text |Cite
|
Sign up to set email alerts
|

Closed Genome Sequence of Escherichia coli K-12 Group Strain C600

Abstract: Escherichia coli strain C600 is a prototypical K-12 derived laboratory strain which has been broadly used for molecular microbiology and bacterial physiology studies since its isolation in 1954. Here, we present the closed genome sequence of E. coli strain C600, retrieved from the American Type Culture Collection (ATCC 23724).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Conjugation assay was conducted to resolve the EC121 conjugative plasmids. In the mating pair, strain EC121 was the donor strain, whereas E. coli K-12 derived strains, J53 [71] and C600 [72], resistant to sodium azide, were the recipient strains. Conjugation was performed using overnight cultures of the donor and the recipient strains grown in LB, in the proportion of 1:2, respectively.…”
Section: Conjugation Assaymentioning
confidence: 99%
“…Conjugation assay was conducted to resolve the EC121 conjugative plasmids. In the mating pair, strain EC121 was the donor strain, whereas E. coli K-12 derived strains, J53 [71] and C600 [72], resistant to sodium azide, were the recipient strains. Conjugation was performed using overnight cultures of the donor and the recipient strains grown in LB, in the proportion of 1:2, respectively.…”
Section: Conjugation Assaymentioning
confidence: 99%
“…However, we note their ability to potentially (re-)acquire Stx through Stx-phage infection (Mellmann et al, 2008). In this study, we applied LRT technology (Koren et al, 2013;Allue-Guardia et al, 2018b) and provide closed genomes and comprehensive phylogenomic analyses for representative Stx (−) NSF O157:H7 and SF O157:NM strains in our collection that tested negative for stx, or were cured of their Stx-phage inventory in our laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis, we chose three E. coli strains that are useful for different applications. E. coli C600 is a lab strain ( 42 , 43 ), E. coli MG1655 is often used in industrial fermentations ( 44–46 ), and E. coli Nissle 1917 is a probiotic strain ( 5 , 47 , 48 ). We found that phage lysate produced from 10 8 E. coli C600 cells could passage >10 7 variants to E. coli MG1655 and E. coli Nissle 1917 (Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%